Efeito do enriquecimento ambiental no desempenho de frangos de corte - Zaparolli, Cassia Maria Sarturi (2015)
The poultry industry is constantly growing due to new technologies and the health quality conquered in the production chain. Currently, some consumers require that animals be respected during the production period, which does not occur agression to the environment and also achieve a great productive performance. The objective of this study was to assess the effect of enriched environments with different types of perches in the performance of broiler chickens. The experiment was conducted in the Poultry Innovations Laboratory (LINAV) located at the Federal Technological University of Paraná UTFPR - Campus Dois Vizinhos. 345 male and 345 female commercial line Cobb 500 was assessed, distributed in a completely casual design in factorial arrangement 2 x 3 (gender x enrichment) with 5 repetitions each. Environmental enrichments were: 1 control (without enrichment), 2 short wall (mud brick) and 3 iron perches with wooden stand and adjustable height. Were assessed weekly indicators of zootechnical performance, mortality, body weight, weight gain and feed conversion, being the information collections of zootechnical performance conducted at ages 7, 14, 21, 28, 35 and 42 days. The variables were analyzed by analysis of variance (ANOVA) using Bayesian Inference 5% probability. It was concluded that environmental enrichment showed improvement in zootechnical indicators only for females. However other studies should be conducted with environmental enrichments considering the zootechnical performance and not just animal welfare indicators.